Mitochondrial Dysfunction in Parkinson's Disease: Pathogenesis and Neuroprotection - Ross B. Mounsey; Peter Teismann (Parkinson's Disease)
Mitochondria are vitally important organelles involved in an array of functions. The most notable is their prominent role in energy metabolism, where they generate over 90% of our cellular energy in the form of ATP through oxidative phosphorylation. Mitochondria are involved in various other processes including the regulation of calcium homeostasis and stress response. Mitochondrial complex I impairment and subsequent oxidative stress have been identified as modulators of cell death in experimental models of Parkinson's disease (PD). Identification of specific genes which are involved in the rare familial forms of PD has further augmented the understanding and elevated the role mitochondrial dysfunction is thought to have in disease pathogenesis. This paper provides a review of the role mitochondria may play in idiopathic PD through the study of experimental models and how genetic mutations influence mitochondrial activity. Recent attempts at providing neuroprotection by targeting mitochondria are described and their progress assessed.